Fetoscopic insufflation of heated‐humidified carbon dioxide during simulated spina bifida repair is safe under controlled anesthesia in the fetal lamb. (19th January 2022) - Joyeux, Luc; Basurto, David; Bleeser, Tom; Van der Veeken, Lennart; Vergote, Simen; Kunpalin, Yada; Trigo, Lucas; Corno, Enrico; De Bie, Felix R.; De Coppi, Paolo; Ourselin, Sebastien; Van Calenbergh, Frank; et al.
Abstract: Objective: To assess the safety of Partial‐Amniotic‐Insufflation‐of‐heated‐humidified‐CO2 (hPACI) during fetoscopic spina bifida repair (fSB‐repair). Method: A simulated fSB‐repair through an exteriorized uterus under hPACI was performed in 100‐day fetal lambs (term = 145 days) under a laboratory anesthesia protocol ( n = 5; group 1) which is known to induce maternal‐fetal acidosis and hypercapnia. Since these may not occur clinically, we applied a clinical anesthesia protocol ( n = 5; group 2), keeping maternal parameters within physiological conditions, that is, controlled maternal arterial carbon dioxide (CO2) pressure (pCO2 = 30 mmHg), blood pressure (≥67 mmHg), and temperature (37.1–39.8°C). Our superiority study used fetal pH as the primary outcome. Results: Compared to group 1, controlled anesthesia normalized fetal pH (7.23 ± 0.02 vs. 7.36 ± 0.02, p < 0.001), pCO2 (70.0 ± 9.1 vs. 43.0 ± 1.0 mmHg, p = 0.011) and bicarbonate (27.8 ± 1.1 vs. 24.0 ± 0.9 mmol/L, p = 0.071) at baseline. It kept them within clinically acceptable limits (pH ≥ 7.23, pCO2 ≤ 70 mmHg, bicarbonate ≤ 30 mm/L) for ≥120 min of hPACI as opposed to ≤30 min in group one. Fetal pO2 and lactate were comparable between groups and generally within normal range. Fetal brain histology demonstrated fewer apoptotic cells and higher neuronal density in the prefrontal cortex in group two. There was no difference in fetal membrane inflammation, which was mild. Conclusion: Fetoscopic insufflation of heated‐humidified CO2 during simulated fSB‐repair through an exteriorized uterus can be done safely under controlled anesthesia. Key points: What's already known about this topic? There is experimental concern that Partial‐Amniotic‐CO2 ‐Insufflation (partial amniotic CO2 insufflation [PACI]) could induce fetal acidosis and hypercapnia as well as damage to the fetal membranes and brain Heated‐humidified PACI is clinically used for fetoscopic spina bifida (SB) repair and has been shown to lessen fetal acidosis and hypercapnia in the fetal lamb What does this study add? In the fetal lamb, heated‐humidified PACI during simulated fetoscopic SB repair through an exteriorized uterus under controlled anesthesia avoids significant fetal acidosis and hypercapnia Moreover, it does not induce substantial changes in fetal brain and membranes histology